Singaporean disability love stories: unpacking perceptions, experiences, and cultures of romantic love amongst people with disabilities in Singapore - Shanthni, S. (Nanyang Technological University, 2025)
The social model of disability – which argues that disability is a product of social and environmental barriers in society that disables – is a key player in advocating for greater disability inclusion in society and subverting previous understandings of disability as an inherent flaw. However, this model fails to articulate if and how disabled people perceive, experience, and navigate barriers in private domains such as romantic love. Furthermore, Singapore provides a unique context to investigate disabled beliefs on romantic love and potential barriers to accessing romantic love, given (1) the strong political presence in facilitating romantic love and marriage in Singapore (e.g. the tying of public housing in Singapore to marriage), and (2) Singapore’s predominantly dominant narrative of state-led disability inclusion in Singapore, which excludes discourse on romantic love. This paper argues that having limited knowledge on and platforms to advocate for romantic love inclusion coupled with strong political presence in love creates a situation of immense pressure to seek love but encountering barriers to securing love as a result of disability. To explore this assertion, this paper intends to examine (1) if and how disabled people in Singapore perceive romantic love and barriers to accessing romantic love, and (2) if there are barriers to accessing romantic love that are unique in Singapore. In doing so, this paper examines the effectiveness of applying the social model as a framework to explain disability and romantic love. These questions are unpacked through in-depth interviews with 13 disabled people and 4 able-bodied people who do disability-related work, supported by journal entries from disabled people who preferred a nonverbal mode of data collection. The study found the following: (1) disabled people in Singapore experienced “self-imposed” barriers and “cultural” barriers, (2) they experienced barriers unique to Singapore such as incompatibility between disability and Singapore’s pragmatic and fast-paced “culture of love”, which supported the paper’s hypothesis. However, the study also found that disabled people in Singapore circumvented these pressures and barriers through various strategies such as religion, rejection of online dating, developing friendships, and rejecting Singapore’s “culture of love”. This study puts forth potential recommendations to improve disability inclusion in the context of romantic love.